Study of blood donor profile in a blood bank attached to a medical college hospital - a retrospective study - Dr. Nidhi Rajendra; Dr. Prashanth Madapura V (Tropical Journal of Pathology and Microbiology, 2017)
Background: Blood Transfusion Services (BTS) are the vital part of modern health care system without which efficient medical care is impossible. To make blood donation safe and increase the confidence of the masses in voluntary blood donation, many safety measures are implemented by the blood transfusion community. The most important of all safety measures is donor selection. Stringent, meticulous and serious donor screening is necessary to afford protection to blood donors and recipients. Aim & Objectives: The aim of this study was to document the current rate and reasons for donor deferral in our tertiary care Centre. Materials and Methods: This retrospective record based study was carried out for whole blood donors at Dr. B R Ambedkar Medical College Hospital Blood bank. Results: In our study the majority of the registered donors were replacement donors (92.2%). Total 2556 people registered for donating blood during the study period (5 years), of whom 2140(83.7%) were males. 176 donors were deferred by medical officer based on detailed medical history and brief physical examination of donors with regard to hemoglobin (Anaemia), blood pressure (hypertension), temperature (hyperthermia/fever), and pulse irregularity and rate. The majority of donors were deferred for temporary reasons (61.3%) and others were permanently deferred. Conclusion: The donor deferral rates and reasons for deferral for blood donation are important issues to be highlighted among blood donors, general public, in the blood banks and hospitals. We can add a significant number of donors by recruiting back a large number of temporarily deferred donors by remotivating them after addressing the reason for deferral.